Dictionary of Upriver Halkomelem - Galloway, Brent Douglas (Book collections on Project MUSE., 2009)
An extensive dictionary (almost 1800 pages) of the Upriver dialects of Halkomelem, an Amerindian language of B.C., giving information from almost 80 speakers gathered by the author over a period of 40 years. Entries include names and dates of citation, dialect information, phonological, morphological, syntactic, and semantic information, domain memberships of each alloseme, examples of use in sentences, and much cultural information.